Applying microwave vacuum pyrolysis to design moisture retention and pH neutralizing palm kernel shell biochar for mushroom production. (September 2020) - Wan Mahari, Wan Adibah; Nam, Wai Lun; Sonne, Christian; Peng, Wanxi; Phang, Xue Yee; Liew, Rock Keey; Yek, Peter Nai Yuh; Lee, Xie Yi; Wen, Ou Wei; Show, Pau Loke; Chen, Wei-Hsin; Chang, Jo-Shu; et al.
Graphical abstract: Highlights: Microwave vacuum pyrolysis produces highly porous palm kernel shell biochar. Biochar retains and increases moisture content in mushroom substrate up to 99%. Biochar speed ups full colonization of the mycelium within one month. Biochar maintains optimum pH level (6.8–7) during the mycelium colonization period. Biochar produces high mycelium growth (up to 91%) and mushroom yield (up to 280 g). Abstract: Microwave vacuum pyrolysis of palm kernel shell was examined to produce engineered biochar for application as additive in agriculture application. The pyrolysis approach, performed at 750 W of microwave power, produced higher yield of porous biochar (28 wt%) with high surface area (270 cm 2 /g) compared to the yield obtained by conventional approach (<23 wt%). Addition of the porous biochar in mushroom substrate showed increased moisture content (99%) compared to the substrate without biochar (96%). The mushroom substrate added with biochar (150 g) was optimal in shortening formation, growth, and full colonization of the mycelium within one month. Using 2.5% of the biochar in mushroom substrate desirably maintained the optimum pH level (6.8–7) during the mycelium colonization period, leading to high mycelium growth (up to 91%) and mushroom yield (up to 280 g). The engineered biochar shows great potential as moisture retention and neutralizing agent in mushroom cultivation.